(untitled) (UNED Research Journal, 2014)
Level of compliance of Costa Rican public institutions in the elaboration and implementation of Institutional Environmental Management Programs. In Costa Rica, the State is one of the largest buyers and its potential impacts on the environment from resource consumption, waste generation and emissions are considerable. Every Costa Rican public institution is required by MINAE Executive Decree No. 36499 (issued in 2011) to develop and implement an Institutional Environmental Management Program (IEMP) to mitigate and control the impacts resulting from their organizational work. The aim of this study was to analyze the level of compliance of Costa Rican public sector institutions in the elaboration and implementation of the IEMP. Available records were consulted at the Ministry of Environment and Energy (MINAE), dividing the institutions into 4 categories: a) ministries; b) decentralized public sector institutions; c) decentralized territorial public sector; and d) other. An on-site assessment tool was then applied in 44 institutions, to determine the level of implementation. As of March 2013, 36.24% of public institutions had submitted an IEMP, with ministries scoring highest on compliance (83.3%). A higher level of implementation was identified for: adoption of an environmental policy, formalization of committees in charge of environmental management work, and systematization of consumption records. There is a need to strengthen staff training and awareness, along with internal disclosure of the IEMP, and incorporation of environmental criteria into the procurement of goods and services, among others. The mean score for the institutions was 70.16 (on a scale of 0 - 100). No significant difference was found between the categories of institutions (t-Student; p = 0.684). The lack of clarity in the application of punitive mechanisms, the low environmental commitment in many institutions and the lack of resources (human and financial) allocated to environmental actions could be affecting compliance with the decree.